Teaching Translation from Spanish to English Worlds Beyond Words - Beeby-Lonsdale, Allison (Didactics of Translation, 1996)
While many professional translators believe the ability to translate is a gift that one either has or does not have, Allison Beeby Lonsdale questions this view. In her innovative book, she demonstrates how teachers can guide their students by showing them how insights from communication theory, discourse analysis, pragmatics, and semiotics can illuminate the translation process. Using Spanish to English translation as her example, she presents the basic principles of translation through 29 teaching units, which are prefaced by objectives, tasks, and commentaries for the teacher, and through 48 task sheets, which show how to present the material to students.